A Study On Causative Factors Of Cost Overrun In Construction Projects In Mogadishu, Somalia - Ibrahim, Ahmed Kasim; Yasin, Mohd Norazam Bin; Hassan, Mohamed Hussein (Tropical Scientific Journal, 2023)
Objective: The construction industry in Somalia has been witnessing enormous expansion and development in recent years, which has resulted in cost overruns. The majority of the cost overruns caused by the construction sector are not adequately managed. Cost overrun is one of the issues confronting the construction industries in Somalia. Investors are becoming increasingly concerned about the issue of cost overruns, which calls for careful attention and in-depth study to be conducted to bring up potential solutions to this problem. This research examined and evaluated causative factors and strategies to overcome cost overrun in construction projects in Somalia especially the capital city of Mogadishu. Research Method: A quantitative approach was adopted in carrying out this research. The target population was 127 Grade A contractors and the sample size was 96 respondents. A questionnaire was sent to the contractor companies registered with the Ministry of Public Works and Reconstruction in Somalia. A total of 60 completed questionnaires were returned. Descriptive statistics (measure of central tendency), and the Relative Importance Index (RII) were used to analyze the data. Findings: The findings of this study indicated that materials, project manager, contractor's management, and unforeseen ground conditions management are major causes of cost overrun. The majority of respondents believe that the reasons for the construction project's cost overrun as well as potential solutions are the same. For instance, problems with the materials, such as the escalation of material prices, problems with the project manager's inexperience and incapability, problems with the contractor, such as the financial difficulties faced by the contractor, and unforeseen problems with the ground conditions, such as the employer being claimed for additional payment. Originality: Therefore, this result helps the parties of the construction industries and policymakers who seek to overcome cost overruns in construction projects in Mogadishu, Somalia